Development of a tool to assess in-situ curing of Foamed Bitumen Mixtures - Kuna, Kranthi; Airey, Gordon; Thom, Nick (Elsevier, 2016)
This paper discusses the simplest yet crucial mix design consideration of Foamed Bitumen Mixtures (FBMs); curing. The objective of the present study is to attain better understanding of the curing mechanism of FBMs and lessen the gap between laboratory curing and field evolution of these mixtures. This was achieved by carrying out a laboratory curing study in two phases. The first phase aimed to understand the curing mechanism and to interpret the level of impact of factors such as temperature and time on the curing of FBMs. The effect of these factors on curing was evaluated with reference to stiffness gain and water loss of FBM specimens. The second phase was intended to develop a tool to assess in-situ curing of FBMs. With a view to assessing in-situ strength (or stiffness) the applicability of the maturity method, which is commonly used to estimate in-situ compressive strength of concrete before removal of formwork, to FBMs was evaluated. A strong correlation was found between maturity and the stiffness values obtained from the laboratory tests which resulted in development of maturity-stiffness relationships. The application of the method to assess the in-situ stiffness was presented using three hypothetical pavement sections. The results illustrate the influence of ambient temperature and the importance of cement addition to FBMs.